Analisis Keterkaitan Industri Minyak Mentah Indonesia Dengan Pertumbuhan Ekonomi di Indonesia Tahun 1990 - 2013 - Dedy Firmansyah, Muhammad; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 6, Juni 2015 (pp. 608 - 745), 2015)
Economic growth is a matter of the economy in the long run and is influenced by various factors. Economic growth also is a condition in which the development of the Gross National Product (GNP), which reflects the growth of output per capita and rising living standards. The purpose of this study was to analyze the association of Indonesian crude oil industry with economic growth in Indonesia in 1990 - 2013 simultaneously and partially and determine which variables are the most dominant influence on economic growth in Indonesia in 1990 - 2013. The analysis technique used in this research is the analysis of multiple linear regression. The results showed Indonesian crude oil production, net exports of crude oil Indonesia, inflation, and the US dollar exchange rate effect simultaneously to economic growth in Indonesia in 1990 - 2013. From the results of partial test result that the Indonesian crude oil production variables, net exports of crude oil Indonesia, inflation, and the United States dollar exchange rate partially positive and significant effect on economic growth in Indonesia in 1990 - 2013. The analysis showed economic growth in Indonesia during the period 1990 - 2013 is more affected by inflation than the Indonesian crude oil production, net exports of crude oil Indonesia, and the US dollar exchange rate. This is evident from the results of the estimation that inflation is more dominant variables and provide a positive and significant effect.
Keywords: Economic Growth, Crude Oil, Net Exports, Inflation, and the US Dollar exchange rate